Transforming Growth Factor-β3/Recombinant Human-like Collagen/Chitosan Freeze-Dried Sponge Primed With Human Periodontal Ligament Stem Cells Promotes Bone Regeneration in Calvarial Defect Rats - Huang, Shiyi; Yu, Fenglin; Cheng, Yating; Li, Yangfan; Chen, Yini; Tang, Jianzhong; Bei, Yu; Tang, Qingxia; Zhao, Yueping; Huang, Yadong; Xiang, Qi (Frontiers in Pharmacology, 2021)
Patients with a skull defect are at risk of suffering Cerebrospinal fluid (CSF) leaking and ascending bacterial meningitis by over 10% per year. Treatment with stem cell has brought great hope to large-area cranial defects. Our laboratory has found that TGFβ3 can promote the osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs), so we designed hybrid TGF-β3/ recombinant human-like collagen (RHC) /chitosan (CS) freeze-dried sponge (TRFS) loading hPDLSCs to repair the skull defect of rats. According to the results of swelling degree, water absorption and moisture retention, CFS with 2% CS was selected. The CFS formed a porous three-dimensional structure observed by scanning electron microscope (SEM). In addition, Cytotoxicity experiment and calcein-AM/PI staining showed that TRFS has good cellular compatibility and can be degraded completely at 90 d in the implantation site. Furthermore, in the rat skull defect models, the bone healings were evaluated with micro-CT. Bone volume and bone volume fraction were higher in the TRFS loaded with hPDLSCs (TRFS-h) group than in controls (P<0.01, vs CFS or TRFS alone). Immunohistochemical results indicated that the expression of Runx2, BMP-2 and COLⅠcells surrounding bone defect in experimental group were higher than that in other groups (P<0.01, vs CFS or TRFS alone). Taken together, hPDLSCs could proliferate and osteogenic differentiation in the TRFS (P<0.05), and TRFS-h could accelerate bone repair in calvarial defect rats. Our research revealed hPDLSC could be good seeded cell for skull injury and its osteogenesis differentiation can be accelerants induced by TGFβ3. Maybe it would be an effective therapeutic strategy for restoring traumatic defect of skull in the future.